2019
DOI: 10.1186/s13046-019-1127-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II promotes ovarian cancer spheroid formation and metastasis by upregulation of lipid desaturation and suppression of endoplasmic reticulum stress

Abstract: Background Angiotensin II (ANGII) and its receptor (AGTR1) have been proposed as significant contributors to metastasis in multiple cancers. Further, high AGTR1 levels are associated with poor epithelial ovarian cancer (EOC) outcomes. However, the mechanistic basis for these effects is unknown. Recent studies have suggested that ovarian cancer metastasis is highly dependent on the formation of multicellular spheroids (MCS). To understand the associations between the ANGII/AGTR1 pathway and cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 59 publications
(59 reference statements)
0
46
0
Order By: Relevance
“…Furthermore, AGTR1 overexpression has also been linked to multiple human malignancies including ovarian, renal, pancreatic, breast, and brain [8] , [9] , [10] , [11] . While in breast cancer (BCa), significant overexpression of AGTR1 represents a subpopulation of Human epidermal growth factor (HER2)-negative and estrogen receptor (ER) positive patients [12] , in ovarian cancer its high expression has been linked to metastasis by promoting multicellular spheroid formation [13] . Mechanistically, overexpression of AGTR1 has been observed to inhibit apoptosis while promoting angiogenesis, cell proliferation and inflammation [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AGTR1 overexpression has also been linked to multiple human malignancies including ovarian, renal, pancreatic, breast, and brain [8] , [9] , [10] , [11] . While in breast cancer (BCa), significant overexpression of AGTR1 represents a subpopulation of Human epidermal growth factor (HER2)-negative and estrogen receptor (ER) positive patients [12] , in ovarian cancer its high expression has been linked to metastasis by promoting multicellular spheroid formation [13] . Mechanistically, overexpression of AGTR1 has been observed to inhibit apoptosis while promoting angiogenesis, cell proliferation and inflammation [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…In GC, the utility of AGTR1 inhibitor signi cantly suppress GC cell proliferation and stromal brosis [28]. It has been proved that AGTR1 could enhance malignant phenotype of several cancer cells to promote tumor progression [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Zhang et al [ 99 ] obtained convergent results indicating that high AT1 expression was negatively correlated with survival time for grade 1 and 2 ovarian tumor patients. Ang II was again found to increase OC cell proliferation by AT1 receptor, but the results were significant only in the 3D culture model.…”
Section: Ovarian Diseases Related To the Ace2/ang-(1-7)/mas1 Axismentioning
confidence: 99%
“…Secretion of Ang II by ovarian cells was observed in in vitro cell lines, xenograft mouse models, and patient samples. Zhang et al [ 99 ] suggest that AGTR1 activates ERK and AKT signaling, as well as transactivation of the EGFR pathway. Furthermore, Gene Ontology (GO) analysis showed that Ang II upregulated multiple SREBP pathway-related genes and downregulated genes of JNK cascade.…”
Section: Ovarian Diseases Related To the Ace2/ang-(1-7)/mas1 Axismentioning
confidence: 99%
See 1 more Smart Citation